The efferent cardiac lymphatic pathways in the macaque monkey - Eliskova, M; Eliska, O; Miller, A J; Palmer, A; DeBoer, A; Usman, Z (Lymphology, 1992)
In ten postmortem hearts of the Macaque monkey (M. mulatta), the coronary lymphatics were visualized using an India ink suspension in 2% gelatin. The left coronary lymphatic initially passed to the dorsal surface of the aortic arch. In five hearts, this lymphatic went directly to the cardiac lymph node, whereas in the others, it first ascended to the left superior tracheobronchial node and then interconnected with the cardiac lymph node. The right coronary lymphatic usually passed in front of the ascending aorta and common arterial (brachiocephalic) trunk and entered the cardiac lymph node. In two hearts, however, the right coronary lymphatic first ascended to an anterior transverse mediastinal node and from here lymphatics joined the cardiac lymph node. Those lymphatics that passed cephalad from the cardiac lymph node to the right anterior mediastinal nodes and the right paratracheal nodes ultimately emptied into the right venous angle. Those lymphatics that passed cephalad from the cardiac lymph node to the anterior transverse mediastinal nodes ultimately emptied into the left venous angle. In five other Macaque monkeys (M. mulatta and M. fascicularis) after marker injection (T1824 blue dye and micropulverized barium sulfate) into the living heart or pericardium, lymphatic drainage beyond the base of the heart could not be demonstrated. Whereas postmortem morphologic studies suggest that the monkey coronary lymphatic system is amenable to obstruction by removal of the cardiac lymph node and interruption of its adjacent lymphatic connections, effective methods for visualizing the mediastinal lymphatic collecting system in the living monkey must be developed before experimental cardiac lymphatic ablation can be accomplished in this species.
Keywords: Macaca fascicularis; Lymph Nodes; Animals; lymfatické uzliny; Macaca mulatta; Lymphatic System; lymfatický systém; zvířata; Heart; Mediastinum; srdce; mediastinum